The Effect of Video-Based Tasks in Listening Comprehension of Iranian Pre-intermediate EFL Learners - Sarani, Abdullah; Behtash, Esmail Zare; Nezhad Arani, Saieed Moslemi (GIST – Education and Learning Research Journal, 2014)
This study aims at finding the effect of video-based tasks in improving the listening comprehension ability of Iranian pre-intermediate EFL (English Foreign Language) learners. After determining the level of learners, an experimental and control group, each of 20 participants, were nominated to contribute to the study. From the time the pre-test was administered to each group, the experimental group was taught by a course of instruction based on video tasks for teaching listening comprehension. The control group was directed by a course of instruction only based on audio materials. Paired Samples T-test computation was utilized by SPSS software to calculate the level of significant difference in pre- and post-tests. Results show that teaching listening on the basis of video-based tasks has a significant effect on learners’ listening comprehension in realizing and understanding the authentic language more effectively.